Helminthiasis in vicuñas (Vicugna vicugna) in the district of Contumaza (Cajamarca, Peru) - Curay C., Joao (2022)
The aim of this study was to estimate the prevalence and burden of gastrointestinal helminths in vicuñas in the district of Contumaza, Cajamarca, as well as to determine their association with the variables of age and sex and to identify the parasitic genera. During August 2015, 208 vicuñas were trapped in the chaccu organized by the peasants and faeces were collected from the rectum. The samples were analysed using the qualitative techniques of flotation with Sheather’s solution and spontaneous sedimentation to detect the presence of helminth eggs and Fasciola hepatica, respectively. The parasite load was estimated using the modified McMaster method. In addition, larvae culture was made with the Baermann technique. The prevalence of helminths was 81.3 ± 5.3% and the prevalence of Strongylus-type eggs, Nematodirus, Trichuris, Capillaria and Moniezia was 61.1, 39.4, 26.9, 16.8 and 8.7% respectively. F. hepatica eggs were not found. The logistic regression test determined that age was a risk factor for the presence of helminths (p<0.05) where vicuñas <1 year and 1-3 years old presented 7.99- and 4.59-fold higher risk of presenting helminths than vicuñas >3 years. The mean parasitic load of nematodes ranged from 103.8 to 121.3 epg, corresponding to a slight load. The genera of infective larvae of the Trichostrongylidae family identified were Cooperia, Trichostrongylus, Ostertagia, Oesophagostomum, Haemonchus and Bunostomum.